PRELIMINARY VIEWS OF MENTAL DEFECT - Akbarov Sardorjan Sadiqjan (Galaxy International Interdisciplinary Research Journal, 2023)
This article presents the attitude of mentally retarded children over the centuries and the opinions of scientists and experts. The emergence of humanistic tendencies towards the mentally retarded during the Renaissance is highlighted.